Use of dignity therapy in palliative care: a comprehensive scoping review - Romel Jonathan Velasco Yanez; Erilaine de Freitas Corpes; Judith Sixsmith; Ana Fátima Carvalho Fernandes; Priscila de Souza Aquino; Régia Christina Moura Barbosa Castro; Herla Maria Furtardo Jorge (BMC Palliative Care)
Abstract Introduction Dignity Therapy is an innovative intervention designed to alleviate emotional suffering and address the distress associated with loss of dignity in individuals with advanced illness or at the end of life. Its use has steadily increased, and previous systematic reviews have synthesized evidence on its effectiveness in palliative care. However, there is no comprehensive synthesis that explores aspects of this intervention beyond commonly reported clinical outcomes. The aim of this review was to identify and synthesize the available evidence on the use of Dignity Therapy in palliative care. Methods This comprehensive scoping review followed the Joanna Briggs Institute methodology, and the final report was prepared in accordance with the PRISMA-ScR checklist. The protocol was registered on the Open Science Framework (DOI: https://doi.org/10.17605/OSF.IO/MNWUJ ). From 2016 onward, systematic searches were conducted in 11 databases, including gray literature. Study selection was performed using RAYYAN software, and qualitative content analysis was used for data analysis. Results Of the 815 records identified, 82 articles with 11 Gy literature documents included. Most studies were published in 2023 (19.5%), originated from the United States (23.1%), used an experimental design (29.2%), and focused on oncology (58.5%). Nine key categories emerged from the analysis: feasibility, acceptability, satisfaction, and effectiveness; perceived health benefits; impact on family; adaptation to diverse contexts; use of technology; economic feasibility; professional profiles; and implementation in underrepresented populations. Conclusions The evidence suggests benefits across various dimensions of health, including among family members, pediatric and adolescent populations, and traditionally underrepresented groups, as well as its implementation in early stages of illness and posthumous delivery. The expansion of Dignity Therapy has also driven cultural and linguistic adaptations, the development of derivative tools, and its application in a range of clinical contexts, along with the involvement of a broader spectrum of professionals. This review provides a comprehensive synthesis to guide healthcare professionals on the current state of knowledge, while identifying key research gaps and new insights to inform future studies.